2002
DOI: 10.1086/341410
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Abnormalities in Dengue Hemorrhagic Fever: Serial Investigations in 167 Vietnamese Children with Dengue Shock Syndrome

Abstract: The pathophysiological basis of hemorrhage in dengue infections remains poorly understood, despite the increasing global importance of these infections. A large prospective study of 167 Vietnamese children with dengue shock syndrome documented only minor prolongations of prothrombin and partial thromboplastin times but moderate to severe depression of plasma fibrinogen concentrations. A detailed study of 48 children revealed low plasma concentrations of the anticoagulant proteins C, S, and antithrombin III, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
195
7
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(231 citation statements)
references
References 20 publications
12
195
7
17
Order By: Relevance
“…Evidence has suggested that severe DENV infection leads to suppressions on circulating native anticoagulants protein C and antithrombin III (22,23), pathological changes partly in accordance with our warfarinized hypercoagulable mouse model (7). Accordingly, we postulated a "two-hit" model in which DENV-elicited anti-DR4 Igs synergize with the DENV-induced suppression of vascular anticoagulants, exacerbating consumption of coagulant factors.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Evidence has suggested that severe DENV infection leads to suppressions on circulating native anticoagulants protein C and antithrombin III (22,23), pathological changes partly in accordance with our warfarinized hypercoagulable mouse model (7). Accordingly, we postulated a "two-hit" model in which DENV-elicited anti-DR4 Igs synergize with the DENV-induced suppression of vascular anticoagulants, exacerbating consumption of coagulant factors.…”
supporting
confidence: 78%
“…Thrombomodulin is crucial in activating vascular anticoagulation processes for preventing the development of a hypercoagulable state (38,39). Soluble circulating thrombomodulin was detected in patients with DHF, potentially contributing to endothelial damage and increasing shock severity (22). In this study, treatments with anti-NS1 Ig, anti-NS1-DR4 Ig, and anti-SP-DR4 Ig suppressed the mRNA and surface expression of thrombomodulin (Fig.…”
Section: Anti-ns1-dr4 Ig Induces Endothelial Abnormalitiesmentioning
confidence: 53%
“…21,22 Reports also show that the activation of complement factor C3 followed by binding of C5b-9 complex to platelet surface is significantly linked with platelet destruction and thrombocytopenia in these patients. [23][24][25] 11 of 61 patients studied by Mitrakul et al, had destruction as a main cause for thrombocytopenia, as revealed by platelet kinetic study. A low MPV implies marrow suppression as a cause of thrombocytopenia and a rising MPV heralds the improvement in platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Our patient met the WHO criteria for DHF and showed abnormalities compatible with bone marrow suppression, and DIC, although major hemorrhagic manifestations were not observed. The probable immunological mechanism was suggested by the wide spectrum of laboratorial abnormalities: a low level of C3 complement, positive antinuclear antibodies, positive cryoglobulins and elevated ADA in serositis.…”
Section: Discussionmentioning
confidence: 67%